Validity and Practicality of Problem Based Learning (PBL) Model Learning Tools to Improve Students’ Conceptual Understanding - Hidayati, Siti; Susilawati, Susilawati; Harjono, Ahmad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aimed to develop a valid and feasible problem-based learning tool to improve students’ conceptual understanding. This research is a development research using the 4D model. In addition to developing science teaching materials, this research also develops syllabus, lesson plans, and concept understanding instruments. This research was conducted in one of the SMPN Lombok Timur. The validation of learning products was carried out by three validators, media experts and material experts. Expert validation data analysis was carried out using the Pearson validation formula. The results of the feasibility study of integrated student worksheet obtained an average value of 80.6% with very valid criteria. The syllabus got an average score of 77.8%, lesson plans got an average score of 78.2%, and the instrument got an average score of 78%. The average learning tools got an average score of 78.75%. The results of practicality obtained an average practicality of the teacher and student questionnaire responses of 78.75%, while the learning implementation sheet was 77.66%. In conclusion, problem-based learning model learning tools were valid and practical to improve students’ conceptual understanding.